Topical doxycycline foam 4% for prophylactic management of epidermal growth factor receptor inhibitor skin toxicity: an exploratory phase 2, randomized, double-blind clinical study - Shacham Shmueli, Einat; Geva, Ravit; Yarom, Nirit; Hubert, Ayala; Keynan, Rita; Kedem, Tal H.; Eini, Meir; Tamarkin, Dov; Shirvan, Mitchell (Supportive care in cancer, 2019)
Purpose Acneiform rash, a common toxicity of epidermal growth factor receptor inhibitors (EGFRIs), can cause patient discomfort, warranting changes in treatment. This study investigated the safety, tolerability, and efficacy of a novel doxycycline foam, FDX104 4%, for managing EGFRI-related skin toxicity. Methods This was an exploratory phase 2, randomized, double-blind, placebo-controlled study. Subjects had metastatic colorectal cancer and were being treated with either cetuximab or panitumumab plus chemotherapy. Treatment (twice-daily topical FDX104 4% on one side of the face and vehicle foam on the other for 5 weeks) was initiated 7 ± 3 days prior to EGFRI therapy. Rash severity, safety, and tolerability were evaluated at 2 and 4 weeks after EGFRI start. Results The mean maximal rash grade was lower with FDX104 4% vs vehicle, and fewer subjects developed moderate-to-severe (grades 2–3) rash. On the Global Severity Score scale, a statistically significant difference favored FDX104 4% over vehicle ( P = .047). Adverse events (AEs) ( n = 68) occurred in 20 subjects; most were mild or moderate. The most common AEs were oral mucositis, nausea, and vomiting, common to chemotherapy and EGFRI treatment. Study-drug–related AEs were experienced by five subjects and consisted of mild, local skin reactions. No study-drug–related systemic side effects were reported. Conclusion Twice-daily, topical administration of FDX104 4% as an adjunct to either cetuximab or panitumumab was safe and well tolerated, and appeared to prevent the onset of rash, especially severe rash. ClinicalTrials.gov identifier Trial Registration NCT02239731